Organizational commitment among intercollegiate head athletic trainers: examining our work environment - Winterstein, A P (Journal of athletic training, 1998)
To 1) examine the commitment of head athletic trainers to their intercollegiate work environments, 2) develop a model that better reflects the head athletic trainer's daily work setting, and 3) use new techniques to describe the various ways head athletic trainers demonstrate commitment to their organizations. Organizational commitment (OC) surveys were sent to 461 head athletic trainers identified for the sample. A response rate of 71.5% (330/461) was obtained from the mail survey. A proportional random sample of head athletic trainers was taken from a population identified in the National Association of Collegiate Directors of Athletics (NACDA) directory of intercollegiate athletics as Division I, II, and III institutions. Returned OC surveys were analyzed using descriptive and inferential statistics for all demographic and OC variables. Exploratory cluster analysis was performed to examine naturally clustering groups. Exploratory cluster analysis revealed five naturally clustering groups that represent the head athletic trainers' patterns of commitment across the specific organizational targets. Paired t tests indicated that the continuance commitment scores were significantly lower than the affective and normative scores across the sample. Analysis of variance tests indicated significant differences for specific commitment dimensions based on gender and NCAA division demographics. Beyond that, the five-cluster solution revealed no particular demographic characteristics that predisposed individuals to specific clusters. THE FINDINGS REINFORCE A CENTRAL THEME IN INTERCOLLEGIATE ATHLETIC TRAINING: that student-athletes and student athletic trainers are the primary focus of the head athletic trainers' commitment. Positive attachment and obligation directed toward student-athletes and student athletic trainers link the five clusters. Commitment patterns in areas other than student-athletes and student athletic trainers define the cluster membership or head athletic trainer "type" presented in this study. In addition, specific commitment differences based on gender and NCAA division may warrant further investigation.